Dinamika Kebijakan Seleksi Pimpinan Perguruan Tinggi Keagamaan Islam Negeri - Zainal Abidin (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to reveal the dynamics of the Ministry of Religious Affairs' policies in selecting and appointing State Islamic Higher Education (PTKIN) Rectors. This study used a qualitative approach. In addition to the Minister of Religious Affairs Regulation, data were collected from online sources. All data were grouped thematically, and a comparative analysis was carried out to discover the dynamics of the policy mechanism for the selection and appointment of the Rector/Chairperson of PTKIN. This study concludes that there are changes to the requirements for educational qualifications and available academic positions for Rector' UIN Rector candidates who were originally doctors and Associate Professors to become doctors and Professors. The PTKIN Senate no longer selects the top three candidates but only gives qualitative considerations. A Selection Commission formed by the Minister of Religious Affairs processes the selection process. The change in PMA from PMA 45/2006 to PMA 68/2015 does not change the position of the Minister of Religious Affairs as the party with full authority to appoint the Rector/Chairperson of PTKIN. Studi ini bertujuan untuk mengungkap dinamika kebijakan Kementerian Agama dalam mekanisme seleksi dan pengangkatan Rektor/Ketua PTKIN. Studi ini menggunakan pendekatan kualitatif. Selain Peraturan Menteri Agama, data-data dikumpulan dari sumber online. Semua data dikelompokkan secara tematik dan dilakukan analisis komparatif untuk menemukan dinamika kebijakan mekanisme seleksi dan pengangkatan Rektor/Ketua PTKIN. Studi ini mengungkap bahwa terdapat perubahan syarat kualifikasi pendidikan dan jabatan fungsional akademik calon Rektor UIN yang semula doktor dan Lektor Kepala menjadi doktor dan Guru Besar. Senat PTKIN tidak lagi menyeleksi dan memilih tiga besar calon, melaikan sebatas pemberi pertimbangan kualitatif. Proses seleksi dilakukan oleh Komisi Seleksi yang dibentuk oleh Menteri Agama. Perubahan PMA dari PMA 45/2006 hingga PMA 68/2015 tidak mengubah posisi Menteri Agama sebagai pihak yang berwenang penuh untuk mengangkat Rektor/Ketua PTKIN. Kata Kunci: Seleksi Rektor, Dinamika Kebijakan, PTKIN